Determinants of Social Security Participation in the Informal Sector: The Role of the Human Development Index and Regional Infrastructure - Nugraha Pratama (Outline Journal of Economic Studies, 2026)
Purpose: This study aims to determine the influence of the Human Development Index and Regional Infrastructure on the Coverage of Employment Social Security Participation in the Informal Sector using sample data from 34 provinces in Indonesia for the 2022-2024 period. Methods: The research method used is a quantitative approach with panel data regression analysis.  Result: The analysis results indicate that the Human Development Index and Regional Infrastructure have a positive and significant effect on the coverage of social security participation for informal sector. Conclusions: A high Human Development Index will have a positive impact not only on individual welfare but also on expanding the coverage of employment social security programs. Infrastructure development will also facilitate and broaden access to social security services and enhance an individual's economic capacity to participate. Originality: This research provides a novel contribution by empirically testing and confirming that the variables of the Human Development Index and Regional Infrastructure are determining factors for social security participation in the hard-to-reach informal sector segment. These findings enrich the literature with a structural perspective that offers more integrated policy solutions.